Earthenware Change in Southern Scandinavia : The Case of Lund, 1150–1350 - Johansson, Erik ; 0000-0002-4820-4673 (Lund Studies in Historical Archaeology, 2026)
This doctoral thesis investigates mediaeval earthenware production, distribution and consumption based on material from Lund, Sweden, moving beyond simple technological shifts to explore the interplay of material factors, social practices, and economic influences. It presents a typology of hard greyware, redware and glazed redware, as well as the chemical analysis of circa 400 samples. The study argues that changes in pottery– particularly the rise of glazed redware jugs – were not driven by isolated innovations but rather by interconnected activities, reshaping consumption patterns. This thesis also highlights the relatively slow response of hard greyware practices to the collapse of Baltic ware traditions around 1200, in which several functions previously held by the diverse Baltic ware, likely became replaced with containers of different materials. Cooking functions were only partially replaced by smaller hard greyware pots. Wine consumption among merchants played an important role in the emergence of glazed redware jugs, but the increase, from approximately 1200 onwards, is attributed not to wine or new techniques but to a widening distribution, increased general usage, and subsequent pressure on producers and distributors – effectively creating a denser network of material dependencies. Statistical analysis suggests deliberate adaptation by potters to meet diverse demands. Furthermore, this research highlights the marginalized status of potters within medieval society, evidenced by their low social standing and the relative lack of value attributed to pottery as a material. This underscores the deeply embedded nature of pottery production practices. Changes in production were linked to shifts in consumption patterns, notably the decline of round-based pots, potentially representing a transition from household industry to more centralized workshops. Spatial analysis of pottery production sites, informed by pXRF-PCA, demonstrates a contraction and relocation of hard greyware production, correlating with a shift towards tripod vessels in the late thirteenth century. Ultimately, this research demonstrates that changes in ceramic practices were deeply intertwined with broader social, economic, and cultural transformations within Lund’s sphere of consumption.
Keywords: Earthenware; Ceramics; Pottery; Lund; Scandinavia; Medieval; Middle Ages; Practice Theory; Entanglement; Material Change; Typology; Chemical Analysis; XRF; ICP; Medieval Archaeology; Historical Archaeology; Glazed redware; Greyware